2008
DOI: 10.1590/s1519-69842008000300025
|View full text |Cite
|
Sign up to set email alerts
|

Haematological changes in Nile tilapia experimentally infected with Enterococcus sp.

Abstract: This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
5
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 25 publications
10
55
5
8
Order By: Relevance
“…It has been shown that in viral and bacterial infections, leukocytosis, lymphocytosis and neutropenia are dominant results in haematologic profiles of the infected fish [23,48]. Unlikely, the reduction of leukocytes and lymphocytes as well as the increase of neutrophils and myelocyts were seen in long time starvation [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in viral and bacterial infections, leukocytosis, lymphocytosis and neutropenia are dominant results in haematologic profiles of the infected fish [23,48]. Unlikely, the reduction of leukocytes and lymphocytes as well as the increase of neutrophils and myelocyts were seen in long time starvation [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of data obtained for individual diseases may provide valuable information on the specific responses in pathophysiological processes of the disease [2,23,34,35,41,48].…”
Section: Introductionmentioning
confidence: 99%
“…These were subjected to five different concentrations of the pesticides namely, Glyphosate (Round up), Paraquat (Gramoxone), Butachlor (Rizene) and Atrazine. Each herbicide had concentrations labeled T0, T1, T2, T3, T4, T5 and T6 as described by Beitlich (1995), FAO (1997) and Martins et al (2008). The concentrations were sub lethal, which is lower than their LC50, earlier determined by Ada (2011).…”
Section: Methodsmentioning
confidence: 94%
“…The recommended dose of MS-222 on Nile tilapia was 130 mg/L (4) while the suitable dose of AGO was 700 mg/L. Generally, the hematological parameters; Hb, Hct, RBC, and WBC of resting fish are approximately 6 g/dL, 26%, 1 × 10 6 cells/µL, and 15 × 10 3 cells/µL, respectively (44,45). In the present study, the hematological parameters of anesthetized Nile tilapia with AGO and MS-222 were higher than the normal level.…”
Section: Discussionmentioning
confidence: 99%